THE IMPACT OF PEDAGOGICAL ASSESSMENT ON THE IMPROVEMENT OF EDUCATION QUALITY - Ozodova Muqaddas (Western European Studies, 2025)
Pedagogical assessment is one of the most essential tools that contribute to the formation of learning motivation, the development of students' personal qualities, and the enhancement of the educational process's effectiveness. It not only reflects students' level of knowledge but also influences their attitude toward studying, self-esteem, and future success. In the context of the modernization of the education system, pedagogical assessment must meet contemporary requirements, taking into account students' psychological development, individual needs, and educational goals. However, in practice, the opposite situation is often observed: instead of encouraging students to engage more deeply with the subject, assessment can cause stress, lower self-confidence, and even lead to a loss of interest in learning.
Keywords: stress; influences; most